The Long Non-Coding RNAs: A New (P)layer in the “Dark Matter” - Derrien, Thomas; Guigó, Roderic; Johnson, Rory (Frontiers in Genetics, 2012)
The transcriptome of a cell is represented by a myriad of different RNA molecules with and without protein-coding capacities. In recent years, advances in sequencing technologies have allowed researchers to more fully appreciate the complexity of whole transcriptomes, showing that the vast majority of the genome is transcribed, producing a diverse population of non-protein coding RNAs (ncRNAs). Thus, the biological significance of non-coding RNAs (ncRNAs) have been largely underestimated. Amongst these multiple classes of ncRNAs, the long non-coding RNAs (lncRNAs) are apparently the most numerous and functionally diverse. A small but growing number of lncRNAs have been experimentally studied, and a view is emerging that these are key regulators of epigenetic gene regulation in mammalian cells. LncRNAs have already been implicated in human diseases such as cancer and neurodegeneration, highlighting the importance of this emergent field. In this article, we review the catalogues of annotated lncRNAs and the latest advances in our understanding of long non-coding RNAs.